PENGUATAN INTEGRITAS HAKIM MELALUI PENYEDIAAN SARANA PENUNJANG KEGIATAN PERADILAN - Tanti Kirana Utami; M. Rendi Aridhayandi; Henny Nuraeny (Universitas Suryakancana, 2023)
In the Joint Decree of the Chairman of the Supreme Court of the Republic of Indonesia and the Chairman of the Judicial Commission of the Republic of Indonesia Number: 047/KMA/SKB/IV/2009 and 02/SKB/P.KY/IV/2009 Concerning the Code of Ethics and Code of Conduct for Judges. Furthermore, in the Guidelines for Enforcement of the Code of Ethics and Code of Conduct of Judges, especially Chapter II Article 4 regulates the obligations and prohibitions for Judges which are elaborated into 10 (ten) principles of the Code of Ethics and Code of Conduct for Judges Judges, namely: Behave fairly; Behave honestly; Be wise and prudent; Be independent, not dependent on others; Have high integrity; Be responsible; Uphold self-esteem (not despicable, not disgraceful, not corrupt); Uphold the rights of others; Uphold the rights of others. high self-esteem (not disgraceful, not violating the law, social norms, and/or religious norms); Highly disciplined; Behave humbly; Be professional. humble; Be professional. In this case in support the realization of Judges who meet the Code of Ethics and Code of Conduct for Judges, one of which needs to be supported with facilities and infrastructure as supporting court activities can affect the performance of the Judges. The availability of facilities and infrastructure with good quality, is needed by every organization everywhere in carrying out its activities to achieve the expected goals. In organizing its activities to achieve the expected goals, including in the courts. Including in the courts.Keywords: Judges; Integrity; Facilities and Infrastructure.